KEWAJIBAN PPAT MEMBUAT LAPORAN BULANAN - , ANDI HAKIM FAISAL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PPAT (Official Competent to Draw Up a Deed of Land) has an important role in peopleâs life, mainly related to land, because PPAT is authorized to make the authentic deeds relating to displacement of land rights. In carrying out their duties, PPAT are responsible for the deeds that have been made. Form of its responsibilities is to make a monthly report of the deeds that have been made to the related parties. The purpose of this essay is to understand the establishment of PPATâs monthly report, to whom monthly report addressed, and sanctions for PPAT who break the rules regarding this monthly report. Based on the results of internship, monthly report made by PPAT addressed to the Head of the Tax Office, Head of the Land and Building Tax Office, Head of the Land Office and the Head of the Regional Office. The monthly report shall submitted no later than 10th of the following month. PPAT who not submitted monthly report could be penalized, like fined or be dismissed from their duties.